2021
DOI: 10.1002/aenm.202100185
|View full text |Cite
|
Sign up to set email alerts
|

Synchrotron X‐Ray Absorption Spectroscopy and Electrochemical Study of Bi2O2Se Electrode for Lithium‐/Potassium‐Ion Storage

Abstract: The increasing demand from portable electronics, electric vehicles, and renewable energy storage/conversion has created great opportunities for developing high-performance and scalable energy storage systems. [1] Potassium-ion batteries (PIBs) that are attractive for abundant potassium resources and low standard reduction potential (−2.93 V vs K + /K) can be a promising alternative energy storage system for lithium-ion batteries (LIBs) whose lithium resources are currently limited by the high market price. [2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…A remarkable example for PIBs is the work of Guo's group. [97] They probed the potassium/lithium storage mechanism of conversion-type Bi Generally speaking, the edge absorption spectrum has a higher correlation with the height of the white peak or the absorption area. [98] Similarly, the valence state of Se is indicated as divalent by Se K-edge XANES.…”
Section: In Situ Xasmentioning
confidence: 99%
See 1 more Smart Citation
“…A remarkable example for PIBs is the work of Guo's group. [97] They probed the potassium/lithium storage mechanism of conversion-type Bi Generally speaking, the edge absorption spectrum has a higher correlation with the height of the white peak or the absorption area. [98] Similarly, the valence state of Se is indicated as divalent by Se K-edge XANES.…”
Section: In Situ Xasmentioning
confidence: 99%
“…A remarkable example for PIBs is the work of Guo's group. [ 97 ] They probed the potassium/lithium storage mechanism of conversion‐type Bi 2 O 2 Se/graphite (Bi 2 O 2 Se/G) anode and found that its potassium storage was superior to lithium storage. The redox reactions, charge transfer process and local atomic structure changes were also unveiled through in situ XAS.…”
Section: In Situ Characterization Techniquesmentioning
confidence: 99%
“…Bi 2 O 2 Se was investigated as advanced anodes for lithium‐ion batteries and potassium‐ion batteries, and the mechanism were studied by in situ Bi L III ‐edge and Se K‐edge XAS. revealing an insertion‐conversion‐alloying process upon lithiation and the dissolution of Li−Se intermediate phases in the electrolyte [67] …”
Section: In Situ Xas Studies Of Battery Anodesmentioning
confidence: 99%
“…revealing an insertionconversion-alloying process upon lithiation and the dissolution of LiÀ Se intermediate phases in the electrolyte. [67]…”
Section: In Situ Xas Studies Of Conversion-type Anodesmentioning
confidence: 99%
“…Such information will be highly valuable as it will reveal the evolution of 3D architecture electrodes during electrochemical processes and elucidate their electrode degradation mechanisms. [ 119–125 ] Thus, these advanced characterization results will guide further optimization of 3D architecture electrodes. Currently, a single structural unit of a 3D architecture electrode is typically selected as the research subject of an in situ microscopy characterization.…”
Section: Challenges and Perspectivesmentioning
confidence: 99%